(untitled) (Research, Society and Development, 2021)
The objective of this paper is to report a didactic experience with active methodologies in a training course for mathematics teachers in the National Training Plan for Basic Education Teachers (PARFOR). The work was developed in two meetings with 20 teachers in training in the city of Itacoatiara, in the state of Amazonas. The active methodologies approached were the hybrid teaching model rotation by stations and peer instruction. The underlying theoretical framework is Pierre Rabardel’s Instrumental Approach, with a focus on Instrumental Genesis, which studies the transformation of an artifact into an instrument. For the methodological path, we rely on the construction of a didactic sequence inspired by the principles of the methodologies themselves. The investigation, qualitative in nature and outlined as an action research, had as instruments direct observation, application of questionnaires with open and closed questions and photographic records of each step of the activity. The results achieved allowed us to conclude that, despite some difficulties with the mathematical concepts addressed, the teachers actively participated in the activities, promoting extensive discussions with their peers and showed great commitment to learning the content and willingness to integrate such methodologies in their teaching practice. It was also found that most teachers were able to achieve the process of instrumentalization and that the dynamic environment provided by the active methodologies contributed to the instrumentation.